STRATEGI MENGATASI KESULITAN SISWA DALAM MENJAWAB SOAL HOTS PADA PEMBELAJARAN BAHASA INDONESIA - Kartika Meilani; Na’imahtul Zakiyah Dwi Wardhani; Aulia Fitriana Adrian; Geby Chrilda Putri Abdi; Silvina Noviyanti; Ahmad Syarif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze effective strategies to overcome students' difficulties in answering Higher Order Thinking Skills (HOTS) questions in Indonesian language learning. The main problem lies in students’ low ability in critical, analytical, and creative thinking when processing text-based information. This research employed a qualitative approach with a descriptive method. The subjects were junior high school students who experienced difficulties in answering HOTS questions. Data were collected through observation, interviews, and documentation. The results indicate that students' difficulties are caused by a lack of conceptual understanding, limited exposure to HOTS-based questions, and learning methods that still emphasize memorization. Effective strategies to address these issues include implementing problem-based learning, utilizing interactive learning media, and providing varied and contextual HOTS exercises. In addition, the teacher’s role in providing scaffolding and feedback is crucial in improving students' higher-order thinking skills. The implementation of appropriate strategies can significantly enhance students' ability to answer HOTS questions in Indonesian language learning.